COMPARATIVE EFFICACY OF URSODEOXYCHOLIC ACID AND DEXAMETHASONE IN REDUCING SEVERE PRURITUS IN PATIENTS WITH INTRAHEPATIC CHOLESTASIS OF PREGNANCY : JPUMHS; 2024:14:04, 243-249. http://doi.org/10.46536/jpumhs/2024/14.04.581 - Shagufta Naz1, Nafeesa Ghani2, Farzana Burki3, Asma Mumtaz4, Andaleeb Farooq5, Asma Aziz6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: Intrahepatic cholestasis of pregnancy (ICP) is a hepatobiliary condition associated with impaired bile acid flow, which results in heavy maternal pruritus and an increased risk of adverse fetal outcomes such as preterm birth and stillbirth. Ursodeoxycholic acid (UDCA) is the first-line therapy, which reduces levels of bile acids and alleviating symptoms. In some cases a poor response to UDCA necessitates additional therapies. Dexamethasone, a corticosteroid, had been proposed as an alternative, however its use during pregnancy remains controversial and concerns exist regarding both its efficacy and safety. OBJECTIVE: To compare the efficacy and safety of ursodeoxycholic acid (UDCA) and dexamethasone in reducing severe pruritus in pregnant women diagnosed with intrahepatic cholestasis of pregnancy (ICP). MATERIAL & METHODS: This was a comparative, prospective study carried out in the Gynecology Department of Hayatabad Medical Complex, Peshawar, from June 2022 to May 2023. A total of 155 pregnant women with ICP whose diagnosis was based on clinical presentation of pruritus and elevated serum bile acid levels (>10 µmol/L) after the 20th week of gestation were included in this study. RESULTS: VAS pain scores decreased significantly in both groups over 4 weeks, however Group A (UDCA) diminished to a greater extent at all time points. At Week 1, the VAS score in Group A was lower than in Group B (6.2 ± 0.9 in group A vs. 7.1 ± 1.0 in group B). By Week 4, Group A mean VAS pain score decreased to 2.1 ± 0.6 and was significantly lower than Group B 3.9 ± 0.8. CONCLUSION: In patients with ICP, UDCA showed substantially superior efficacy compared to dexamethasone with respect to severe pruritus and serum bile acid levels. The UDCA group had better maternal and fetal outcomes, as well as a more favorable safety profile confirming its place as the first-line therapy for ICP management.